The Impact of Laissez Faire Leadership Style and Communication on Employee Performance at Retail Companies in Sidoarjo, Indonesia - Anggreta Queen Lorena; Misti Hariasih (Indonesian Journal of Law and Economics Review, 2019)
The purpose of this study was to determine the effect of laisse faire leadership style, work discipline and communication on the performance of the employees of PT. Trans Retail Sidoarjo partially and simultaneously and to find out the most significant influence among variables laissez faire leadership style, workadiscipline andacommunication. This study took 86 samples with non-probability samplingatechniques, especially saturated samplingausing multiple linear regression analysis and classic assumption tests withaSPSS version 18. Thissstudy uses quantitative methods, surveys and explanatory research. The results of this study indicate that there is an influence of laissez faire leadership style, work discipline and a communication simultaneously and partially on employee performance and the laissez faire leadership stylea variable is the most influential variable on employee performance.